The Relationship Between the Level of Adequate Nutrition and Endurance in Physical Education Students - Agung Nugroho; Mawardinur; Andy Prayogy; Syuhadi; Dicka Ardanta (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
The aim of this research is to find out whether there is a relationship between the level of nutritional adequacy and endurance in physical education students. In this research the method used is descriptive research with a correlational research type and a quantitative approach. The sample in this study was 37 physical education students. The data in this study was obtained from a 24-hour food recall questionnaire, and endurance data was taken using a 1,600 meter running test to measure endurance in physical education students. Data analysis in this study was assisted using the SPSS 26 application to determine the relationship between variables. From the analysis carried out, the following results were obtained for variable Durability).